A Metal‐Free Strategy to Release Chemisorbed H2 from Hydrogenated Boron Nitride Nanotubes1. Issue 46 (11th August 2014) - Roy, Lisa; Bhunya, Sourav; Paul, Ankan
Abstract Chemisorbed hydrogen on boron nitride nanotubes (BNNT) can only be released thermally at very high temperatures above 350 °C. However, no catalyst has been identified that could liberate H2 from hydrogenated BN nanotubes under moderate conditions. Using different density functional methods we predict that the desorption of chemisorbed hydrogen from hydrogenated BN nanotubes can be facilitated catalytically by triflic acid at low free‐energy activation barriers and appreciable rates under metal free conditions and mildly elevated temperatures (40–50 °C). Our proposed mechanism shows that the acid is regenerated in the process and can further facilitate similar catalytic release of H2, thus suggesting all the chemisorbed hydrogen on the surface of the hydrogenated nanotube can be released in the form of H2. These findings essentially raise hope for the development of a sustainable chemical hydrogen storage strategy in BN nanomaterials.